2021
DOI: 10.3390/bdcc5030031
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for Customer Identification Service Model Based on Distributed Ledger Technology to Transfer Virtual Assets

Abstract: Recently, cross-border transfers using blockchain-based virtual assets (cryptocurrency) have been increasing. However, due to the anonymity of blockchain, there is a problem related to money laundering because the virtual asset service providers cannot identify the originators and the beneficiaries. In addition, the international anti-money-laundering organization (the Financial Action Task Force, FATF) has placed anti-money-laundering obligations on virtual asset service providers through anti-money-launderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, they did emphasise that identification and prosecution was subject to strict adherence to Customer Due Diligence (CDD) and Know Your Customer (KYC) regulations on the part of cryptocurrency exchanges. Effective implementation of this would allow law enforcement agencies to rely upon the information collected to trace transactions, so the importance of collecting and verifying customer information has led to KYC verification systems being proposed, to reduce cost and combat money laundering (Moyano and Ross, 2017; Park and Youm, 2021).…”
Section: Regulatory Issues Associated With Blockchainmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did emphasise that identification and prosecution was subject to strict adherence to Customer Due Diligence (CDD) and Know Your Customer (KYC) regulations on the part of cryptocurrency exchanges. Effective implementation of this would allow law enforcement agencies to rely upon the information collected to trace transactions, so the importance of collecting and verifying customer information has led to KYC verification systems being proposed, to reduce cost and combat money laundering (Moyano and Ross, 2017; Park and Youm, 2021).…”
Section: Regulatory Issues Associated With Blockchainmentioning
confidence: 99%
“…Trozze et al (2022) focused on fraud-related financial crimes and concluded that Ponzi/high-yield investment programme schemes and ICO scams were the most common cryptocurrency frauds at the present time. Greater efforts are being made by law enforcement agencies to identify and detect financial crimes committed using cryptocurrencies (Farrugia et al , 2020; Gandal et al , 2018; Grobys, 2021; Kamps and Kleinberg, 2018; Park and Youm, 2021; Rognone et al , 2020; Shi et al , 2019; Sureshbhai et al , 2020).…”
Section: Regulatory Issues Associated With Blockchainmentioning
confidence: 99%